2022
DOI: 10.1021/jacs.1c08485
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Labile Heme in Living Cells Using a Small Molecule Fluorescent Probe

Abstract: Labile heme (LH) is a complex of Fe­(II) and protoporphyrin IX, an essential signaling molecule in various biological systems. Most of the subcellular dynamics of LH remain unclear because of the lack of efficient chemical tools for detecting LH in cells. Here, we report an activity-based fluorescence probe that can monitor the fluctuations of LH in biological events. H-FluNox is a selective fluorescent probe that senses LH using biomimetic N-oxide deoxygenation to trigger fluorescence. The selectivity of H-Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…These results suggest that the heme content in cancer cells may affect their sensitivity to ferroptosis. In addition, as another important executor of heme export, part of ABCG2's heme output capacity was found to be related to ferroptosis in recent studies (Desuzinges-Mandon et al, 2010;Kawai et al, 2022). But there is still no substantive research to support this finding yet.…”
Section: Heme Metabolism and Ferroptosismentioning
confidence: 98%
“…These results suggest that the heme content in cancer cells may affect their sensitivity to ferroptosis. In addition, as another important executor of heme export, part of ABCG2's heme output capacity was found to be related to ferroptosis in recent studies (Desuzinges-Mandon et al, 2010;Kawai et al, 2022). But there is still no substantive research to support this finding yet.…”
Section: Heme Metabolism and Ferroptosismentioning
confidence: 98%
“…27(A)). 169 Compared with probes 39 and 40 , probe 37 showed remarkable fluorescence enhancement in response to LH, and thus the later was selected as the candidate probe. Probe 37 comprised of a rhodol platform bearing an electron-withdrawing 4,4-difluoropiperidine N -oxide moiety, which served as the LH reactive site.…”
Section: Small-molecule Fluorescent Probes For Monitoring Other Bioac...mentioning
confidence: 99%
“…By contrast, the addit Fe 2+ (10 μM) resulted in only a less 10−fold fluorescence increase even after incubati 30 min. Besides, Fe 3+ and hemin (in the absence of GSH) would not affect the detect Interestingly, based on the above−mentioned N−oxide deoxygenation strategy, Hirayama et al [43] further reported a selective fluorescence probe H−FluNox for intracellular labile heme (i.e., complex of Fe 2+ and protoporphyrin IX, an essential protein cofactor), as well as its applications in ferroptosis process. The design of H−FluNox was inspired by the biomimetic reaction of cytochrome P450 with tetramesitylporphyrin iron complex and perbenzoic acid derivatives (Figure 4A) [44], in which the cleavage of O−O bond was accelerated by the electron−withdrawing aryl group.…”
Section: Probes For Fe 2+ and Hemementioning
confidence: 99%